Human Streptococcus suis Outbreak, Sichuan, China - Yu, Hongjie (Centers for Disease Control and Prevention, 2006)
From mid-July to the end of August 2005, a total of 215 cases of human Streptococcus suis infections, 66 of which were laboratory confirmed, were reported in Sichuan, China. All infections occurred in backyard farmers who were directly exposed to infection during the slaughtering process of pigs that had died of unknown causes or been killed for food because they were ill. Sixty-one (28%) of the farmers had streptococcal toxic shock syndrome; 38 (62%) of them died. The other illnesses reported were sepsis (24%) and meningitis (48%) or both. All isolates tested positive for genes for tuf, species-specific 16S rRNA, cps2J, mrp, ef, and sly. A single strain of S. suis caused the outbreak, as shown by the identification of a single ribotype. The high death ratio was of concern; prohibiting backyard slaughtering ended the outbreak.